2007
DOI: 10.1097/yco.0b013e3282c3a5c1
|View full text |Cite
|
Sign up to set email alerts
|

Torture

Abstract: Torture prevention and interdisciplinary rehabilitation of survivors must receive more attention, and healthcare professionals have an obligation to take a substantial role in this effort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 40 publications
0
29
0
2
Order By: Relevance
“…Primary caregivers are the points of first contact and important gatekeepers to recognizing victims and initiating or referring for treatment of specialized centers [10,11]. However, specialists most often field these referrals and are responsible for initiating specialized treatment regimens.…”
Section: Scope Of Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary caregivers are the points of first contact and important gatekeepers to recognizing victims and initiating or referring for treatment of specialized centers [10,11]. However, specialists most often field these referrals and are responsible for initiating specialized treatment regimens.…”
Section: Scope Of Problemmentioning
confidence: 99%
“…For example, PTSD has been well described in almost all torture survivors [10,42]. A full spectrum of psychogenic manifestations from generalized anxiety to major depression has been described [43].…”
Section: Specific Types Of Torture and Their Pain Sequelaementioning
confidence: 99%
“…13,14 A small body of studies focusing specifically on torture survivors has observed high rates of PTSD and depression, but most of these investigations have been based on convenience samples and nonrandom casecontrol designs. 9,[15][16][17] There is value therefore in examining the larger body of epidemiologic surveys in which torture and other PTEs 18,19 are included in the factors assessed to gauge the relative importance of the former type of abuse on mental health among populations exposed to mass conflict.…”
mentioning
confidence: 99%
“…Os sobreviventes de tortura são frequentes nestas populações e muitas vezes passam sem uma deteção adequada (Wenzel, 2007). As sequelas incluem: PTSD, dor crónica, perturbações depressivas e sintomas reativos determinados e baseados na cultura que muitas das vezes não são suficientemente explorados.…”
Section: Exposição a Cenários De Guerra E Violênciaunclassified